2019
DOI: 10.1186/s13287-019-1463-y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic modulation of signaling pathways to expand and maintain the bipotency of human hepatoblasts

Abstract: BackgroundThe limited proliferative ability of hepatocytes is a major limitation to meet their demand for cell-based therapy, bio-artificial liver device, and drug tests. One strategy is to amplify cells at the hepatoblast (HB) stage. However, expansion of HBs with their bipotency preserved is challenging. Most HB expansion methods hardly maintain the bipotency and also lack functional confirmation.MethodsOn the basis of analyzing and manipulating related signaling pathways during HB (derived from human induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Previous studies have demonstrated that stimulation of Wnt and inhibition of TGF-β were both important for hepatic proliferation [7,14,22]. Our recent study correlated with these reports and further demonstrated that Hedgehog signaling is also involved in stemness maintenance and proliferation of HBs [6]. Thus, we kept the TGF-β inhibitor A8301, Wnt agonist CHIR, and Hedgehog activator SAG, while replacing the remaining growth factors (EGF, HGF, and BMP4) with chemicals to optimize the HB culture condition.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Previous studies have demonstrated that stimulation of Wnt and inhibition of TGF-β were both important for hepatic proliferation [7,14,22]. Our recent study correlated with these reports and further demonstrated that Hedgehog signaling is also involved in stemness maintenance and proliferation of HBs [6]. Thus, we kept the TGF-β inhibitor A8301, Wnt agonist CHIR, and Hedgehog activator SAG, while replacing the remaining growth factors (EGF, HGF, and BMP4) with chemicals to optimize the HB culture condition.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, hPSCs-derived HBs show advantages over PHs and reprogramed HPLCs, owing to a wider and more convenient cell source, stronger proliferation ability, and more efficient differentiation into mature hepatocytes [6,8,20]. However, previous reported HB amplification formulations contained growth factors that were unsuitable for large-scale cell production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations